The West Bank and Gaza : Economic Performance, Prospects, and Policies: Achieving Prosperity and Confronting Demographic Challenges. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This is the latest in a series of economic reports by staff economists in the IMF's Middle Eastern Department. This book discusses the latest economic data coming out of the West Bank and Gaza Strip, with a particular emphasis on growing demographic concerns. The work is enhanced by the addition of numerous data tables and graphs, which extensively analyze economic trends in the region.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet